Analisis Pencapaian dimensi Bergotong Royong dalam Pembelajaran Pendidikan Pancasila: Penelitian - Goliked, A.J; Hairida, H; Kresnadi, H (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Education not only provides knowledge today, but also must educate students to become moral people. Therefore, education is not enough to instill cognitive intelligence, but also needs to teach students to become good human beings to build better civil society. The purpose of this study is to describe the achievement of the dimensions of mutual cooperation in learning Pancasila education for grade IV SDN 17 Pontianak City. This research is classified as quantitative descriptive research. The method of analysis used in this study is quantitative descriptive analysis. The subjects of this study were 31 students of class IV SDN 17 Pontianak City. The value of the level of achievement of the mutual cooperation dimension of 81.6% is in the very good category, the value of the achievement of the coloured element of the collaborative element is in the very good category, the value of the achievement of the mutual cooperation dimension of the element of caring by 80% is in the very good category, the value of The level of achievement of the dimensions of mutual cooperation in the sharing element is 76.4% in the good category.